SHOUTING AT THE TELEVISION: ARGUMENTATION STRATEGIES IN SECOND SCREEN SOCIAL MEDIA USE FOR CHILEAN POLITICAL TV SHOWS - Ibarra Herrera, Daniela; Unger, Johann Wolfgang (AoIR Selected Papers of Internet Research, 2016)
In this paper we argue that research into “second-screening” during political TV shows is a useful way of examining broader social trends in politics and society. Using a critical discourse studies framework and drawing on the theoretical frameworks developed by Erving Goffman and Murray Edelman, we compare the argumentation strategies used in tweets related to four Chilean TV shows: Estado Nacional and Ciudadanos, which display tweets on screen during the programme, and Entrevista Verdadera and El Informante, which do not display tweets. The analysis shows that in the tweets related to shows that engage viewers directly by displaying their tweets, viewers directly address the guests and political figures in their tweets, and draw on multimodal resources (infographics, images and videos) and hyperlinks as a form of “evidence” by using _topoi_ (argumentative shortcuts) related to numbers and authority. On the other hand, the tweets from shows that do not directly engage viewers use different strategies to build their arguments, such as taboo language and visual memes, usually used to make _ad hominem_ attacks. We argue that these differing engagement practices by media organisations have the potential to shape the public sphere in particular ways and also require some reconsideration of the boundaries of politics as an object of investigation in social sciences and humanities research.